Four new species of leptonetid spiders (Araneae, Leptonetidae) from Anhui Province, China - Shuhui Li; Qiang Chen; Yanfeng Tong (ZooKeys)
Four new species of leptonetid spiders from Anhui Province, China are recognized: Jingneta qishan Tong, sp. nov. (♂♀), Jingneta wukuishan Tong, sp. nov. (♂), Leptonetela jingde Tong, sp. nov. (♂♀) and Rhyssoleptoneta lishan Tong, sp. nov. (♂♀). An identification key to leptonetid spiders from Anhui is provided.